Binding affinity of pyridines with AmIII/CmIII elucidated by density functional theory calculations. Issue 5 (10th January 2019) - Yu, Jie; Ma, Jun; Yang, Chuting; Yu, Haizhu
Abstract : The binding affinity of Am III /Cm III to a series of pyridines under different concentrations of nitrate were investigated by density functional theory calculations. Abstract : In recent decades, N-heterocyclic ligands have been extensively used in the separation of lanthanides/actinides, whereas the selective extraction of amercium or curium has been very challenging. Using density functional theory calculations, this study is devoted to the investigation of the binding affinity of a series of modelling pyridine ligands with Am III and Cm III . The structure–property correlations between the amercium and curium systems and the binding affinity were obtained, and promising strategies for efficient separation of Am III /Cm III were proposed.